2014
DOI: 10.1038/nrendo.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and IGF receptor signalling in neural-stem-cell homeostasis

Abstract: Neural stem cells (NSCs) are found in two regions in the adult brain: the subgranular zone (SGZ) in the hippocampal dentate gyrus and the subventricular zone (SVZ) adjacent to the lateral ventricles. Similarly to other somatic stem cells, adult NSCs are found within specialized niches that are organized to facilitate NSC self-renewal. Alterations in stem-cell homeostasis can contribute to the consequences of neurodegenerative diseases, healthy ageing and tissue repair after damage. Insulin and the insulin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
108
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 134 publications
(138 reference statements)
6
108
0
1
Order By: Relevance
“…Dietary sea cucumber cerebroside (SCC) extracted from Acaudina molpadioides attenuated hepatic steatosis via inhibition of hepatic lipogenic gene expression and enzyme activity, and enhancement of triglyceride secretion from the liver (157,184,188). SCC inhibited hepatic lipogenic enzymes, including fatty acid synthase, malic enzyme (ME), and glucose-6-phosphatedehydrogenase (G6PDH).…”
Section: Altered Gsl and Sm Levels Affect Liver Steatosis And Insulinmentioning
confidence: 99%
“…Dietary sea cucumber cerebroside (SCC) extracted from Acaudina molpadioides attenuated hepatic steatosis via inhibition of hepatic lipogenic gene expression and enzyme activity, and enhancement of triglyceride secretion from the liver (157,184,188). SCC inhibited hepatic lipogenic enzymes, including fatty acid synthase, malic enzyme (ME), and glucose-6-phosphatedehydrogenase (G6PDH).…”
Section: Altered Gsl and Sm Levels Affect Liver Steatosis And Insulinmentioning
confidence: 99%
“…However, OPC proliferation increases in proximity to demyelinating lesions (17), which are often characterized by vascular barrier disruption (18). In addition, some of the cells in the CNS express peripheralhormone receptors, such as the insulin and mineralocorticoid receptors, which regulate neurogenesis in the adult CNS (19,20). Although the role of vascular barrier disruption in CNS regeneration has not yet been clarified, we hypothesized that vascular barrier disruption mediated by CNS injury induces the leakage of circulating factors into the CNS, resulting in remyelination.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chen et al [14] found no effect of SIRT2 inhibition on brain injury such as amyotrophic lateral sclerosis and ischemic stroke. SIRT2 is closely related to AKT pathway in insulin as well as growth factor-responsive cells [15], and insulin receptor and growth factor receptors are highly expressed in the hippocampus [1617]. In contrast, HDAC inhibitors manipulate the epigenome and affects the expression of only 2% of mammalian genes [18].…”
mentioning
confidence: 99%